First Magnetohydrodynamic Simulations of Jets and Radiative Feedback from a Massive Star - Barquero Alvarado, Joshua (2024)
The study of massive protostars requires the explicit use of numerical simulations that allow us to follow the early stages of events defining the evolution of these stellar objects. This project aims to understand the complex processes occurring within the accretion material falling onto the star and the various dynamics within the molecular cloud. To achieve this, we utilize the state-of-the-art program known as PLUTO, combined with modules enabling us to solve the equations for magnetohydrodynamics, radiation, photoionization, and self-gravity. Consequently, we conduct our study to comprehend the impact of these modules on the star by running different simulations with alternating modules enabled. Finally, we compare the changes these modules induce in the star’s evolution and the final properties of the massive star. Protostellar outflows alone limit stellar mass growth in an accretion scenario with a finite mass reservoir. Radiative feedback dominates the latter stages of stellar formation around the zero-age main sequence. Specifically, we observe that radiation forces restrain gravitational infall toward the disk, affect the magneto-gravito-centrifugal equilibrium, and completely halt stellar accretion, resulting in a star with a mass of approximately 40 M⊙ at around 100 kyr. While photoionization widens the bipolar outflow cavities and reduces the gravitational infall momentum by about 50%, it does not limit stellar mass accretion until later stages, resulting in a star with a mass of approximately 45 M⊙ at around 120 kyr. In contrast, simulations that do not implement radiative interactions from these modules continue to accrete material at this time, and we report masses of approximately 75 M⊙ when negleting radiative force feedback.